Retrieval of 30 Lymph Nodes Is Mandatory for Selected Stage II Gastric Cancer Patients - Chen, Yong-He; Lu, Jun; Nie, Run-Cong; Liu, Dan; Liu, Ai-Hong; Deng, Zi-Jian; Chen, Xi-Jie; Xiang, Jun; Chen, Ying-Bo; Huang, Chang-Ming; Chen, Shi; Peng, Jun-Sheng (Frontiers in Oncology, 2021)
BACKGROUND According to the 8th edition AJCC staging manual, a least of 16 lymph nodes retrieval (LNRs) is the minimal requirement for lymph nodes (LNs) dissection of gastric cancer surgery. Previous studies have shown that increasing the number of LNRs (≥30) prolongs survival for selected patients. However, the necessity of retrieving 30 or more LN for stage II gastric cancer patients is still under debate. AIM This study aims to explore the impact of retrieving 30 or more lymph nodes on the survival of stage II cancer patients. METHODS A total of 1177 patients diagnosed with stage II gastric cancer were enrolled in this study. The clinicopathological parameters and the impact of different LNRs (<30 or ≥30) and positive lymph node ratio (pLNR) on overall survival (OS) were retrospectively analyzed. RESULTS The mean number of LNRs was 34±15. A total of 44% (518/1177) of patients had an LNRs <30, while 56% (659/1177) of patients had an LNRs ≥30. The 5-year survival rate was 81% for all patients, 76% for the LNRs<30 group, and 86% for LNRs≥30 group, respectively (P=0.003). The survival benefit of retrieving 30 lymph nodes was significant in certain subgroups: age>60 years/male/underwent total gastrectomy/stage IIB. For N+ patients, higher pLNR was significantly correlated with poor survival. CONCLUSION The survival benefit of retrieving 30 LNs varies in different subgroups. An LNRs of 30 is mandatory for selected stage II gastric cancer patients.